Prediction of response to obeticholic acid in primary biliary cholangitis: Development and validation of the OCA response score (ORS). (March 2023) - De Vincentis, A.; Terracciani, F.; D'Amato, D.; Invernizzi, P.; Morgando, A.; Vanni, E.; Viganò, M.; Alvaro, D.; Venere, R.; Lleo, A.; Colapietro, F.; Degasperi, E.; et al.
Abstract : Introduction: Obeticholic acid (OCA) is the approved second-line treatment for patients with primary biliary cholangitis (PBC). Biochemical response by POISE criteria is achieved in ∼40% of patients, according to registrative and post-marketing studies. Aim: To derive the OCA response score (ORS) for predicting response to OCA at 12 and 24 months, according to the POISE (alkaline phosphatase(ALP)/upper limit of normal(ULN) <1.67 with a reduction of at least 15%, and a normal bilirubin) and ALP/ULN<1.67 criteria. Materials and Methods: We used the Italian RECAPITULATE database including centers from Italian PBC Registry, the Sicilian PBC Network, the PBC Project Piemonte-Liguria-Valle D'Aosta and CLEO/AIGO PBC study group. Multivariable Cox's regressions with backward selection method were applied to obtain parsimonious predictive models, including pre-treatment variables and/or the change of ALP/ULN and total bilirubin after 6 months' therapy. Discrimination and calibration were evaluated by c-statistics and comparing observed and predicted probabilities, and internally validated with bootstrap resampling procedure. Results: 441 PBC patients (median age 58, women 88%, cirrhosis 34%, median follow-up 24 months) with at least 6 months' observation after of OCA prescription, were included for ORS derivation. The observed 12 and 24 months' response probabilities were 38%, 47% for POISE and 58%, 67% for ALP/ULN<1.67 criteria. A score including age, pre-treatment pruritus, cirrhosis, ALP/ULN, GGT/ULN and bilirubin (ORS), and one that includes also the relative change of ALP/ULN and total bilirubin after 6 months (ORS+), showed good discrimination for response by POISE (c-statistics=0.76 and 0.84, for ORS and ORS+, respectively) and by ALP/ULN<1.67 (c-statistics=0.78 and 0.89, for ORS and ORS+, respectively). Bootstrap validation evidenced modest overfitting (slopes>0.90) and consistent discriminative performance. Mean absolute errors <0.04 were observed for prediction of POISE and ALP/ULN<1.67 response at 24 months according to ORS and ORS+. Conclusions: The ORS accurately predicts OCA response at 12 and 24 months. This will enable to enhance allocation of second-line therapies in PBC with a personalised medicine approach.